Physicochemical cell damage in relation to lethal amphotericin B action. - Beggs, W H (1994)
A direct relationship between the concentration-dependent rate of amphotericin B-induced K+ release from Candida albicans and the concentration-dependent rate of killing by the drug was established. This relationship together with the observed rapidity of both release and killing action supports the conclusion that the lethal action of amphotericin B is primarily physicochemical in nature.